Do perceived norms of social media users' eating habits and preferences predict our own food consumption and BMI?. (1st June 2020) - Hawkins, Lily K.; Farrow, Claire; Thomas, Jason M.
Abstract: In laboratory studies, exposure to social norm messages conveying the typical eating behaviour of others has influenced participants' own consumption of food. Given the widespread use of social media, it is plausible that we are implicitly exposed to norms in our wider social circles, and that these influence our eating behaviour, and potentially, Body Mass Index (BMI). This study examined whether four perceived norms (perceived descriptive, injunctive, liking and frequency norms) about Facebook users' eating habits and preferences predicted participants' own food consumption and BMI. In a cross-sectional survey, men and women university students (n = 369; mean age = 22.1 years; mean BMI = 23.7) were asked to report their perceptions of Facebook users' consumption of, and preferences for, fruit, vegetables, energy-dense snacks and sugar sweetened beverages (SSBs), their own consumption of and preferences for these foods, and their BMI. Multiple linear regression revealed that perceived descriptive norms and perceived frequency norms about Facebook users' fruit and vegetable consumption were significant positive predictors of participants' own fruit and vegetable consumption (both p s < .01). Conversely, perceived injunctive norms about Facebook users' energy-dense snack and SSB consumption were significant positive predictors of participants' own snack and SSB consumption (both p s < .05). However, perceived norms did not significantly predict BMI (all p s > .05). These findings suggest that perceived norms concerning actual consumption (descriptive and frequency) and norms related to approval (injunctive) may guide consumption of low and high energy-dense foods and beverages differently. Further work is required to establish whether these perceived norms also affect dietary behaviour over time.